Plectin - Prechova, Magdalena; Korelova, Katerina; Gregor, Martin (Current biology, 2023)
Prechova et al. introduce the giant cytoskeletal crosslinker protein plectin.
Keywords: Cytoskeletal Proteins; cytoskeletální proteiny; Plectin; plektin